Kepemimpinan Transformasional Kepala Sekolah dalam Penerapan Kurikulum Merdeka - Edo Agustian; Dian Hidayati; Widodo Widodo (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2024)
This study examines the principal's transformational leadership in implementing the Merdeka curriculum at a primary school. Ideally, transformational leadership is an effort to change individuals to achieve the best quality. However, the inability of the principal as a leader to provide stimulus can be feared to hurt the implementation of school activities. The research method used descriptive qualitative research, is a rigorous approach that provides in-depth insights. The location of the research is at SD Muhammadiyah Wirobrajan 1 Yogyakarta. This study's data sources were primary and secondary data sources. Primary data was collected through interviews, while the research subjects comprised two people: the principal and the deputy for curriculum. Secondary data is through observation and documentation. The data analysis technique involves managing, grouping, sorting, marking, and coding, as well as providing data categories so that working hypotheses can be obtained and formulated according to the data obtained. The data analysis procedure is data reduction and concluding. The study results showed that the principal of Muhammadiyah Wirobrajan 1 Elementary School Yogyakarta made efforts to develop suggestions and para Sana, build good relationships with teachers, and realize the school's vision, mission, and academic development through the independent curriculum.